Diseño de una matriz de medidas tendientes a la integración ciudad-movilidad a partir de las componentes ambiental, energética y social - Frediani, Julieta Constanza (2014)
In order to reflect on methodologies that allow new approaches to urban mobility, the present work shows the methodological procedure for the design of a decision making matrix that identifies the relation between the transportation system and the urban-regional system considering the articulation of energy, environmental and social components. To apply the design, the City of La Plata (Argentina) is taken as a study case. In this way, we will show the decision making matrix, on the one hand, and one of the decisions taken, the analysis of the incorporation of a tram, on the other hand, showing the different criteria for their choice and materialization. The development of this methodological design allows an spatial and temporal systematization of the considered measures, which are different depending on type and mode of mobility. This overcomes the traditional approach which considers urban areas as a homogeneous whole, suggesting intervention strategies customized according to the problems and characteristics that define each urban area. The possible replication of this methodology in to other cities is also one of the contributions of this work in pursuit of an inclusive and environmentally sustainable urban transport system.